1965
DOI: 10.1021/ba-1965-0050.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Optical Generation of Hydrated Electrons from Aromatic Compounds

Abstract: A flash photolysis investigation of aromatic compounds has shown that photoionization in aqueous solution occurs for a number of benzene derivatives with electron-donating substituents, aryl carboxylic acids, and hetero cyclics with five-member rings. Thermo dynamic estimates for several benzene deriva tives indicate that electron ejection is feasible and is competitive with bond rupture. It is sug gested that the lowest π-π* state of the ring sys tem populates a charge transfer intermediate which can release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 6 publications
(6 reference statements)
1
21
0
1
Order By: Relevance
“…Single exponential decays were fit to a function of the form I(t) = A exp(-t/T)+B [1] in which I(t) is the calculated intensity at the time t, A is the amplitude, r is the fluorescence lifetime, and B is a baseline parameter. The nonexponential decays could be fit well by the sum of two exponentials, [2] in which T1 and T2 are the lifetimes of the two components and f is the weight of the component having lifetime Tr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single exponential decays were fit to a function of the form I(t) = A exp(-t/T)+B [1] in which I(t) is the calculated intensity at the time t, A is the amplitude, r is the fluorescence lifetime, and B is a baseline parameter. The nonexponential decays could be fit well by the sum of two exponentials, [2] in which T1 and T2 are the lifetimes of the two components and f is the weight of the component having lifetime Tr.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known (2) that irradiation of aqueous tryptophan and other indole derivatives in the 280-nm absorption band leads to the formation of solvated electrons. Although there is still some uncertainty about the yield (3), because of the presence of fast recombination of the ejected electron with the counter radical cation, this photoionization is generally thought to be monophotonic and a major nonradiative pathway (4).…”
mentioning
confidence: 99%
“…Lors de l'excitation de dérivés phénoliques, le processus primaire suivant l'excitation est connu comme faisant intervenir un mécanisme de photo éjection d'électrons à partir de l'état excité du phénol (JOSCHEK et GROSSWEINER, 1966). Un état intermédiaire où les trois espèces radicales phénoxyle-électron-proton sont potentiellement formées est généralement proposé.…”
Section: Influence De L'oxygène Dissous (λ = 254 Nm)unclassified
“…(49,92) The most direct evidence for the existence of this mechanism is derived from flash photolysis studies, which have shown that ultraviolet irradiation of aqueous solutions of indole and its derivatives, including tryptophan, results in formation of solvated electrons. (93,94) While accurate measurements of the quantum yield of solvated electrons will be required to assess the quantitative significance of this mechanism, there is considerable indirect evidence that it may be an important factor in the radiationless deactivation of the indole excited state. The quantum yield of indole in water is strongly temperature dependent.…”
Section: Radiationless Deactivation Of the Excited Statementioning
confidence: 99%